Characteristics of recycled concrete aggregates from precast slab block buildings - Venkrbec, Václav; Nováková, Iveta; Henková, Svatava (IOP Publishing, 2017)
Precast slab block buildings (PSBB) typically and frequently occur in Central and Eastern Europe, as well as elsewhere in the world. Some of these buildings are currently used beyond their service life capacity. The utilization of recycled materials from these buildings with regard to applying the principles of sustainable construction and using recycled materials will probably be significant in the following years. Documentation from the manufacturing processes of prefabricated blocks for precast slab block buildings is not available, and also it is difficult to declare technological discipline during the construction of these buildings. Therefore properties of recycled concrete aggregates (RCA) produced from construction and demolition waste (C&DW) of precast slab block buildings build between 1950s to 1990s are not sufficiently known. The demolition of these buildings is very rare today, but it can be assumed an increase in demolitions of these buildings in the future. The use of RCA in new concrete requires verification/testing of the geometrical and physical properties of RCA according to the EN 12 620+A1 standard. The aim of the contribution is to present a case study of the demolition of slab block building with emphasis on RCA usage. The paper presents the results of the tests according to European standards for determining selected geometrical and physical properties of the RCA. The paper describes and evaluates tests such as determination of particle size distribution - Sieve Analysis, content of fine particles, determination of density and water absorption. The results of the properties testing of RCA are compared with the properties of natural aggregate. The general boundary conditions of RCA particular tests are presented

Precast slab block buildings (PSBB) typically and frequently occur in Central and Eastern Europe, as well as elsewhere in the world. Some of these buildings are currently used beyond their service life capacity. The utilization of recycled materials from these buildings with regard to applying the principles of sustainable construction and using recycled materials will probably be significant in the following years. Documentation from the manufacturing processes of prefabricated blocks for precast slab block buildings is not available, and also it is difficult to declare technological discipline during the construction of these buildings. Therefore properties of recycled concrete aggregates (RCA) produced from construction and demolition waste (C&DW) of precast slab block buildings build between 1950s to 1990s are not sufficiently known. The demolition of these buildings is very rare today, but it can be assumed an increase in demolitions of these buildings in the future. The use of RCA in new concrete requires verification/testing of the geometrical and physical properties of RCA according to the EN 12 620+A1 standard. The aim of the contribution is to present a case study of the demolition of slab block building with emphasis on RCA usage. The paper presents the results of the tests according to European standards for determining selected geometrical and physical properties of the RCA. The paper describes and evaluates tests such as determination of particle size distribution - Sieve Analysis, content of fine particles, determination of density and water absorption. The results of the properties testing of RCA are compared with the properties of natural aggregate. The general boundary conditions of RCA particular tests are presented
Characteristics of recycled concrete aggregates from precast slab block buildings
Keywords: RCA; C&DW; Precast slab block buildings; PSBB; physical properties; RCA; C&DW; Precast slab block buildings; PSBB; physical properties